2019
DOI: 10.3390/cells8050439
|View full text |Cite
|
Sign up to set email alerts
|

2-Oxonanonoidal Antibiotic Actinolactomycin Inhibits Cancer Progression by Suppressing HIF-1α

Abstract: HIF-1 serves as an important regulator in cell response to hypoxia. Due to its key role in promoting tumor survival and progression under hypoxia, HIF-1 has become a promising target of cancer therapy. Thus far, several HIF-1 inhibitors have been identified, most of which are from synthesized chemical compounds. Here, we report that ALM (ActinoLactoMycin), a compound extracted from metabolites of Streptomyces flavoretus, exhibits inhibitory effect on HIF-1α. Mechanistically, we found that ALM inhibited the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In addition to phenolic compounds that can act as antioxidants, others also have anti-inflammatory and immunomodulatory roles. Previous studies on clinical applications reported that the compound 2oxonanone (CAS) plays a role in inhibiting cancer development by suppressing HIF-1α (Cheng et al, 2019). The qualitative identification of C. comatus contains alkaloids, saponins, flavonoids, polyphenol, and phenolic.…”
Section: Results and Discussion Phytochemicals Screening And Identifi...mentioning
confidence: 99%
“…In addition to phenolic compounds that can act as antioxidants, others also have anti-inflammatory and immunomodulatory roles. Previous studies on clinical applications reported that the compound 2oxonanone (CAS) plays a role in inhibiting cancer development by suppressing HIF-1α (Cheng et al, 2019). The qualitative identification of C. comatus contains alkaloids, saponins, flavonoids, polyphenol, and phenolic.…”
Section: Results and Discussion Phytochemicals Screening And Identifi...mentioning
confidence: 99%
“…Although this study is not related to tumors, not even in human cells, this study at least suggests that OIP5-AS1 may regulate HIF1-expression. HIF-1α is ubiquitous in human and mammalian cells and is also expressed under normal oxygen (21% O2) (Cheng et al, 2019;Miska et al, 2019), but the synthetic HIF-1 protein is quickly degraded by the intracellular oxygen-dependent ubiquitin protease degradation pathway (Oh et al, 2016;He et al, 2017), and can be stably expressed under hypoxia (Wang and Semenza, 1995;Salceda and Caro, 1997). It was well know that hypoxia contributes to the Warburg effect through the regulation of expression of HIF-1α (Yang et al, 2014;Liu et al, 2016), whether OIP5-AS1 regulates the Warburg effect in cervical cancer cells through HIF-1α remains uncharacterized.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, using low concentrations of ALM resulted in an enhanced effect of Everolimus, an inhibitor of mTOR already used in anti-cancer therapy. 68 The combination of ALM and Everolimus enables a lower drug dose and more efficient therapy for solid tumor patients. 68 Zebularine, the analog of cytidine belonging to a group of DNA methyltransferases, also shows a downregulation effect on HIF-1α expression.…”
Section: Introductionmentioning
confidence: 99%
“… 68 The combination of ALM and Everolimus enables a lower drug dose and more efficient therapy for solid tumor patients. 68 Zebularine, the analog of cytidine belonging to a group of DNA methyltransferases, also shows a downregulation effect on HIF-1α expression. Using this compound in the study of the human colorectal cancer line (HCT116) and tumor xenografts resulted in the degradation of HIF-1α protein and the reduction of angiogenesis.…”
Section: Introductionmentioning
confidence: 99%